2014
DOI: 10.1021/es504252z
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Chlorine Isotope Analysis to Identify Abiotic Degradation Pathways of 1,1,1-Trichloroethane

Abstract: This study investigates dual C−Cl isotope fractionation during 1,1,1-TCA transformation by heat-activated persulfate (PS), hydrolysis/dehydrohalogenation (HY/DH) and Fe(0). Compound-specific chlorine isotope analysis of 1,1,1-TCA was performed for the first time, and transformation-associated isotope fractionation ε bulk C and ε bulk Cl values were −4.0 ± 0.2‰ and no chlorine isotope fractionation with PS, −1.6 ± 0.2‰ and −4.7 ± 0.1‰ for HY/DH, −7.8 ± 0.4‰ and −5.2 ± 0.2‰ with Fe(0). Distinctly different dual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 68 publications
4
23
0
Order By: Relevance
“…In situations where dissolved PHC plumes are of interest, CSIA data can be used to estimate the extent of in situ biodegradation that has occurred by applying the Rayleigh model (Hunkeler et al ; Aelion et al ) and to assess remedial system effectiveness. Moreover the use of CSIA on two elements of a molecule, the so‐called dual isotope approach (2D–CSIA), can be used to distinguish between processes which can potentially co‐occur during treatment (Fischer et al , ; Palau et al ; Tobler et al ; Vogt et al ). For example, Palau et al () showed significant differences for 2D–CSIA carbon and chlorine fractionation during 1,1,1‐trichloroethane (1,1,1‐TCA) transformation by heat activated persulfate, hydrolysis/dehydrohalogenation, and zero valent iron.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where dissolved PHC plumes are of interest, CSIA data can be used to estimate the extent of in situ biodegradation that has occurred by applying the Rayleigh model (Hunkeler et al ; Aelion et al ) and to assess remedial system effectiveness. Moreover the use of CSIA on two elements of a molecule, the so‐called dual isotope approach (2D–CSIA), can be used to distinguish between processes which can potentially co‐occur during treatment (Fischer et al , ; Palau et al ; Tobler et al ; Vogt et al ). For example, Palau et al () showed significant differences for 2D–CSIA carbon and chlorine fractionation during 1,1,1‐trichloroethane (1,1,1‐TCA) transformation by heat activated persulfate, hydrolysis/dehydrohalogenation, and zero valent iron.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover the use of CSIA on two elements of a molecule, the so‐called dual isotope approach (2D–CSIA), can be used to distinguish between processes which can potentially co‐occur during treatment (Fischer et al , ; Palau et al ; Tobler et al ; Vogt et al ). For example, Palau et al () showed significant differences for 2D–CSIA carbon and chlorine fractionation during 1,1,1‐trichloroethane (1,1,1‐TCA) transformation by heat activated persulfate, hydrolysis/dehydrohalogenation, and zero valent iron. Fischer et al () and Vogt et al () showed the potential of carbon and hydrogen 2D–CSIA to distinguish between aerobic and anaerobic degradation pathways of benzene and toluene, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…3C-D In order to compare the field and laboratory isotope patterns, the isotope data of 1,1,1-314 TCA and 1,1-DCE measured during 1,1,1-TCA transformation by DH/HY in the laboratory 315 (Palau et al 2014b) were reevaluated in this study according to Eq. (1) and (3) (Fig.…”
Section: Calculation Of Substrate Remaining Fraction 207mentioning
confidence: 99%
“…Cl) and 1,1-DCE ( 13 C) from field samples, in 143 conjunction with concentration data, were compared to the isotope patterns determined from a 144 previous laboratory experiment of 1,1,1-TCA transformation by DH/HY (Palau et al 2014b). 145…”
mentioning
confidence: 99%
“…During the last decades 13 C/ 12 C compound‐specific isotope analysis (CSIA) has been demonstrated as an effective analytical tool for assessing degradation of the environmental pollutants . Recently, the use of isotope analysis of two or more elements in the molecule has been proposed in order to obtain additional detailed information on the degradation mechanism of a particular compound . In studying the environmental fate of BOCs, 81 Br/ 79 Br‐CSIA can be used as a complementary tool for assessing the mechanism of BOCs bio/chemical transformations …”
mentioning
confidence: 99%